Treatment of superior mesenteric artery mycotic aneurysm by synthetic vascular graft: a case report - Alam, Syed Muhammad Hammad; Rabia Gilani; Muhammad Ali Adnan; Nida Jawad; Asif Raza; Amber Farman (Journal of the Pakistan Medical Association, 2023)
Superior mesenteric artery (SMA) aneurysm is a rare disease, especially if it is mycotic (infective) in origin. It is difficult to detect the problem during its initial natural course and usually presents in late phase due to its complications such as rupture, dissection, haemorrhage, and mesenteric ischaemia. Initially, the patient present with non-specific symptoms like vague colicky abdominal pain, nausea, vomiting, discomfort, malaise, and low-grade fever but prompt workup and intervention can lead to definitive diagnosis and uneventful outcome. This report describes the case of a 60-year-old male patient who presented with non-specific abdominal symptoms and, on workup, was diagnosed with superior mesenteric artery mycotic aneurysm. It was successfully treated surgically by resection of aneurysm and reconstruction of superior mesenteric artery by inter-positional Polytetrafluoroethylene (PTFE) synthetic vascular graft. Keywords: Infected Aneurysm, Mycotic Aneurysm, Superior Mesenteric Artery, Splanchnic Aneurysm, PTFE (Polytetrafluoroethylene graft)